1、 合并同类项、去括号与添括号 1.根据去括号法则,在 上填上“+”号或“-”号: (1) a (-b+c)=a-b+c; (2) a (b-c-d)=a-b+c+d;(3) (a-b) (c+d)=c+d-a+b;2.已知x+y=2,则x+y+3= , 5-x-y= .3.下列去括号有没有错误?若有错,请改正:(1)a2-(2a-b+c) (2)-(x-y)+(xy-1) =a2-2a-b+c; =-x-y+xy-1.3.去括号:(1)a+3(2b+c-d) = (2)3x-2(3y+2z) =(3)3a+4b-(2b+4a) = (4)(2x-3y)-3(4x-2y) =4.计算(1)a(b
2、c) (2)a(bc)(3)(ab)(cd) (4)(ab)(cd)(5)(ab)(cd) (6)(ab)(cd)5.去括号:(1)a+(-b+c-d) (2)a-(-b+c-d) (3)-(p+q)+(m-n) (4)(r+s)-(p-q)6.化简:(1)(2x-3y)+(5x+4y); (2)(8a-7b)-(4a-5b); (3)a-(2a+b)+2(a-2b); (4)3(5x+4)-(3x-5); (5)(8x-3y)-(4x+3y-z)+2z; (6)-5x2+(5x-8x2)-(-12x2+4x)+2;(7)2-(1+x)+(1+x+x2-x2); (8)3a2+a2-(2a2-2a)+(3a-a2)。(9)5a(3x3y4a) (10)3x(4y2x1)1